E-Commerce Technique Training for Bumdes for Business Development in Mendalo Indah Village, Jaluko District, Jambi - Wiwik Tiswiyanti; Fredy Olimsar; Nela Safelia; Istiqomah Melinda; Dios Nugraha Putra (PT FORMOSA CENDEKIA GLOBAL, 2023)
The service aims to help develop businesses carried out by BUMDes through training in e-commerce techniques in Mendalo Indah Village. The method for achieving goals is carried out through stages; firstly a location survey, the two teams conducted a pre-research to find out the problems faced by partners and finally provided training and practice in using digital applications with e-commerce. Activities are provided to MSMEs and BUMDes administrators. The results are in the form of providing knowledge about digital marketing strategies to partners, and partners are able to utilize digital technology as a platform to increase village original income and the welfare of village communities